Peculiarities of the structure of personality adaptability of medical students studying on a budget basis - Yu. N. Timofeeva (Вестник университета, 2022)
The article is devoted to the study of the features of the personal adaptability structure of 1st year students of a medical university studying on a budgetary basis. The concept of the phenomenon of adaptability is given, various approaches to understanding the structural components of adaptability are analyzed. The study used the method of Kolpakova L.M., which reveals the adaptive attitude of the individual to difficult situations, and the method of Maklakov A.G., which diagnoses the adaptive abilities of the individual. Based on the results of the study, conclusions were drawn about the deficiency of the level of reflective-evaluative, cognitive-emotional components of adaptability and the general level of adaptive abilities of this group of students. The analysis of the behavioral component of adaptability demonstrates the opposite result of its parameters; based on the results of the analysis of the motivational-semantic component, average indicators for both of its parameters were revealed. It has been established that the majority of respondents have signs of character accentuations with a tendency to behavioral reactions of a neurotic type, low emotional stability and signs of a socio-oriented personality orientation.